Genome-wide analysis of the WRKY genes and their important roles during cold stress in white clover - Manman Li; Xueqi Zhang; Tianxiang Zhang; Yan Bai; Chao Chen; Donglin Guo; Changhong Guo; Yongjun Shu (PeerJ, 2023)
Background White clover (Trifolium repens L) is a high-quality forage grass with a high protein content, but it is vulnerable to cold stress, which can negatively affect its growth and development. WRKY transcription factor is a family of plant transcription factors found mainly in higher plants and plays an important role in plant growth, development, and stress response. Although WRKY transcription factors have been studied extensively in other plants, it has been less studied in white clover. Methods and Results In the present research, we have performed a genome-wide analysis of the WRKY gene family of white clover, in total, there were 145 members of WRKY transcription factors identified in white clover. The characterization of the TrWRKY genes was detailed, including conserved motif analysis, phylogenetic analysis, and gene duplication analysis, which have provided a better understanding of the structure and evolution of the TrWRKY genes in white clover. Meanwhile, the genetic regulation network (GRN) containing TrWRKY genes was reconstructed, and Gene Ontology (GO) annotation analysis of these function genes showed they contributed to regulation of transcription process, response to wounding, and phosphorylay signal transduction system, all of which were important processes in response to abiotic stress. To determine the TrWRKY genes function under cold stress, the RNA-seq dataset was analyzed; most of TrWRKY genes were highly upregulated in response to cold stress, particularly in the early stages of cold stress. These results were validated by qRT-PCR experiment, implying they are involved in various gene regulation pathways in response to cold stress. Conclusion The results of this study provide insights that will be useful for further functional analyses of TrWRKY genes in response to biotic or abiotic stresses in white clover. These findings are likely to be useful for further research on the functions of TrWRKY genes and their role in response to cold stress, which is important to understand the molecular mechanism of cold tolerance in white clover and improve its cold tolerance.